Adherence to WHO guidelines of diarrhea management among children under 2 years old in Tikrit city - K. Abedalrahman, Sarab (Tikrit Journal of Pharmaceutical Sciences, 2023)
Diarrhea, has a major impact on global health, due to its high worldwide prevalence and health costs, and because it can be reduced by appropriate interventions and treatment. The aim of this study is to evaluate the adherence of health workers with the WHO guidelines of diarrhea management for children under 2 years old. A cross sectional study, done in 4 primary health care centers and Tikrit Teaching hospital . Three samples tested ; Random sample of 491 mother of under 2 years old child with diarrhea,14 GPand 17 nursing staff in PHCCs, 22 residents and11 nursing staff in Tikrit teaching hospital. Drugs alone or with ORS had given by 90% of all respondents and non-had received ORS alone. About45.5% of the residents and 21.4% of GP prescribe antispasmodic and antiemetic drugs during diarrhea. Only one 4.5% of the residents know that zinc is used in the treatment of diarrhea, and only 21.4% of the GP and 9.1% of the residents know the relation between vitamin A and diarrhea. Only 14.3% of the GPs and 9.1% of the residents didn’t use antibiotics in the management of diarrhea. Only 14.3% of the GPs and 13.6% of residents give correct indication of antibiotic use in diarrhea. Only 70.3% of the PHCC nursing staff and 18.2% of hospital nursing staff mentioned dextrolyt as the best treatment for diarrhea. Conclusion: There is overuse of antibiotics which is due to the wrong knowledge of the health workers.